A Review on Effect of Food on Medication - Priyanka Gupta; Vikas Jharia (Current Research in Pharmaceutical Sciences, 2014)
Medications, both prescription and over-the-counter, are used every day to treat acute and chronic illness. Research and technology constantly improve the drugs we have available and introduce new ones. Medications can help people live healthy lives for a prolonged period. Although medicines are prescribed often, it is important to realize that they must still be used with caution. The effect of drug on a person may be different than expected due to food, beverages, dietary supplements the person is consuming (drug-nutrient/food interaction) or another disease the person has (drug-disease interaction). A drug interaction is a situation in which a substance affects the activity of a drug, i.e. the effects are increased or decreased, or they produce a new effect that neither produces on its own. These interactions may occur out of accidental misuse or due to lack of knowledge about the active ingredients involved in the relevant substances. Regarding food-drug interactions physicians and pharmacists recognize that some foods and drugs, when taken simultaneously, can alter the body's ability to utilize a particular food or drug, or cause serious side effects. It is imperative for pharmacists to keep upto- date on potential drug-food interactions of medications, especially today’s new drugs, so that they may counsel properly and advise patients regarding foods or beverages to avoid when taking certain medications. This fact sheet describes common food/drug and drug/nutrient interactions. We hope this will help to see the potential for interactions to avoid them.